High Frequency Constraints on the Layout of Wide Band Gap-Based Power Electronic Assemblies Within Shielded Enclosures - (:unkn) unknown (My University, 2019)
Since its integration into power electronic converters, the value proposition of wide band gap semiconductors has yet to be holistically realized due to the high frequency effects associated with increased switching speeds. The United States Navy’s Smart Ship System Design (S3D) platform enables the investigation of wide band gap-based devices in shipboard Medium Voltage Direct Current (MVDC) Integrated Power and Energy Systems (IPES) through the use of metaheuristic model-based scaling laws. These physics-based scaling laws are produced from a virtual prototyping approach which takes into account the discrete building blocks associated with multi-cell based power conversion and distribution equipment and can be used to predict size, weight, losses, cost and reliability. In present practice, the discrete building blocks consist of power electronic assemblies laid out and enclosed within shielded enclosures. In an effort to incorporate the high frequency effects associated wide band gap-based Power Electronic Building Blocks (PEBB) into the virtual prototyping approach, a mathematical model which captures the high frequency effects is formulated in this thesis.
Keywords: Multi-objective Optimization MOO; Power Electronics Building Block PEBB; Shipboard Power Systems; Smart Ship System Design S3D; Virtual Prototyping Process VPP; Wide Band Gap WBG